Collaboration between nurses and doctors in the decision‐making process when considering ending the life‐prolonging treatment of intensive care patients - Kristine Gjessing; Simen A. Steindal; Monica Evelyn Kvande (Wiley, 2023)
Abstract Aims The aim of the study was to explore intensive care nurses' collaboration with doctors' when considering ending the life‐prolonging treatment of patients in the intensive care unit. Design A qualitative method with an explorative descriptive design was employed. Methods Data were collected through semi‐structured interviews with four intensive care nurses and four doctors working in three intensive care units at two university hospitals and one local hospital. The data were analysed using systematic text condensation. This study was reported according to the consolidated criteria for reporting qualitative research checklist. Results Two categories were identified in the data analysis: listening to each other during the decision‐making process and continuity and having time to facilitate regular discussions of prognosis and treatment plans.